Interior Hunian Adaptif Banjir di DAS Tukad Badung, Bali - Ni Nyoman Urmila Sari; Dion Eko Prihandono; Putu Surya Triana Dewi (Journal of Creative Student Research, 2026)
This research aims to examine the implementation of adaptive and sustainable interior design strategies for residential buildings in flood-prone areas along the Tukad Badung watershed, Bali. Flooding has significantly affected interior elements such as flooring, walls, furniture, and electrical installations. This study adopts a case study approach using qualitative methods, including literature review, field observations, semi-structured interviews with 14 informants (affected residents, local government representatives, contractors, and academics), and use coding table analysis. The findings reveal that most houses have not yet optimally implemented flood-adaptive interior principles. The materials used are generally vulnerable to water and moisture, spatial layouts do not fully support evacuation or post-flood recovery, and essential installations are often positioned without safe elevation considerations. The recommended adaptive interior design principles include the use of water-resistant and low-absorption materials, elevation of critical interior elements, modular and flexible furniture systems, optimization of natural ventilation and lighting, and spatial zoning that supports mitigation and faster recovery processes. The study concludes that a sustainable interior design approach focusing on resilience, efficiency, and adaptability can significantly reduce flood-related damage and accelerate post-disaster recovery. This research is expected to serve as a reference for interior designers, architects, and communities in developing more resilient housing in flood-prone areas.